What Is Fueling FinTech Lending? The Role of Banking Market Structure - Balyuk, Tetyana; Berger, Allen N; Hackney, John (The Review of Corporate Finance Studies, 2026)
We study the broad question about the sources of FinTech lending growth by examining a specific representative product for which the technologies of both FinTech and the incumbent competitors can be identified and compared—small business lending. We test whether the presence of incumbents employing different technologies affects FinTech penetration, and find more FinTech lending where large/out-of-market banks are more prevalent. Using stress test exposures and Community Reinvestment Act examinations as instruments, we find that FinTech credit more often substitutes for loans by large/out-of-market banks than small/in-market banks. Results are consistent with FinTech advantages in processing hard information, rather than hardening soft information. (JEL G21, G23, O33)